Chinese and Canadian preservice teachers in face-to-face dialogues: Situating teaching in cultural practices for West-East Reciprocal Learning. (February 2023) - Holloway, Susan M.; Xu, Shijing; Ma, Simin
Abstract: This study was contextualized in a Teacher Education Reciprocal Learning Program that has been an essential part of Xu and Connelly's (2013–2020) SSHRC Partnership Grant Project for West-East reciprocal learning in education. Canadian and Chinese preservice teacher education students were given the opportunity to have face-to-face dialogues to enhance their cross-cultural learning and understanding. Our research was to find out the reciprocal learning outcomes through our participant observations, reflections, and follow-up interviews. Both Canadian and Chinese teacher candidates valued this face-to-face interaction, which hopefully has helped open their eyes to view education from others' cross-cultural perspectives and lived experiences with broadened horizons and enhanced global competences.